Human Relation Management Strategy based on SWOT Analysis in Improving Employee Performance - Wibowo, Rudi; Umar, Nonda Elyzza; Faizah, Erna Nur; Majid, Abdul; Fajri, Mega Barokatul (Universitas Negeri Surabaya, 2025)
This study aims to analyze human resource management (HRM) strategies, based on a SWOT analysis, to improve employee performance at CV Cendana, an LPG distribution company. A qualitative approach, using interviews and direct observation, was employed to explore the strengths, weaknesses, opportunities, and threats that affect the effectiveness of HR strategies. The results showed that employee loyalty, harmonious work culture, and flexible organizational structure are the company's main strengths. However, there are still weaknesses such as the absence of a structured training system and undocumented performance evaluations. External opportunities in the form of advances in digital training technology and government support can be utilized to improve training and HR development strategies. Through the mapping of SO, WO, ST, and WT strategies, this research provides applicable strategic recommendations for companies in building adaptive, competitive, and sustainable HR policies.